PELATIHAN PENGENALAN MACHINE LEARNING BAGI SISWA SMK NEGERI 2 PEKANBARU - Taslim, Taslim; Susi Handayani; Walhidayat (Fakultas Ilmu Komputer, 2025)
The machine learning training at SMK Negeri 2 Pekanbaru aims to introduce the basic concepts of machine learning, including Python programming and the use of the Scikit-Learn library. In the era of Industry 4.0, skills in artificial intelligence and machine learning are crucial to prepare students to compete in the workforce and technology sectors. This program was conducted through theoretical and practical methods, incorporating discussions, simulations, demonstrations, and assignments. Evaluations were carried out to measure participants' understanding before and after the training, with results showing significant improvement in students' understanding of basic machine learning concepts, such as algorithms and programming tools. Although most participants showed good understanding, some students still need further material reinforcement, especially regarding the application of machine learning in real projects. This training is expected to enhance students' technical skills and open career opportunities in information technology and artificial intelligence fields. With this program, students are expected to acquire foundational skills that are relevant for competing in the increasingly technology-driven global job market.